Design and numerical parametric study of a compact air-cooled heat exchanger. (18th August 2017) - Huang, Zhiwei; Ling, Jiazhen; Hwang, Yunho; Aute, Vikrant; Radermacher, Reinhard
Abstract : Air-cooled heat exchangers are a main component in air-conditioning and heat pump systems and, therefore, a major research focus. Such heat exchangers, mainly of fin-and-tube and microchannel types, use fins to augment the airside heat transfer area. Recently, it has been shown that finless designs, referring to heat exchangers using < = 2 mm hydraulic diameter bare tube bundles, can deliver better airside heat transfer performance than conventional heat exchangers. In the current study, a novel air-cooled heat exchanger consisting of bifurcated bare tubes with two different tube diameters is proposed. The tubes in the first level split into two or more tubes at certain angles. The secondary tubes then merge back to the first level tube again. The heat transfer and pressure drop characteristics are numerically analyzed using a three-dimensional model and compared with baseline bare tube heat exchangers. The novel bifurcated bare tube heat exchanger was found to have 15% higher airside heat transfer coefficient and 4%∼12% lower airside pressure drop than baseline bare tube heat exchanger with the same diameter (0.8 mm), frontal area, volume, and air velocity (3.5∼5 m/s).